9x(-1)-7=x

Simple and best practice solution for 9x(-1)-7=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x(-1)-7=x equation:


Simplifying
9x(-1) + -7 = x

Reorder the terms for easier multiplication:
9 * -1x + -7 = x

Multiply 9 * -1
-9x + -7 = x

Reorder the terms:
-7 + -9x = x

Solving
-7 + -9x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-7 + -9x + -1x = x + -1x

Combine like terms: -9x + -1x = -10x
-7 + -10x = x + -1x

Combine like terms: x + -1x = 0
-7 + -10x = 0

Add '7' to each side of the equation.
-7 + 7 + -10x = 0 + 7

Combine like terms: -7 + 7 = 0
0 + -10x = 0 + 7
-10x = 0 + 7

Combine like terms: 0 + 7 = 7
-10x = 7

Divide each side by '-10'.
x = -0.7

Simplifying
x = -0.7

See similar equations:

| -7-5[2x-5(10+6x)]= | | -3-x=-2x+8 | | (-0.75x+6)-(2.5x-1.9)= | | 2(3x+2)=2x+1+x | | 100=v+23 | | 7-3x=-4+13 | | 29z+15z+11z+35z+46z+14z= | | (m-n-1)(m-n+1)= | | 25=5r | | x+x+2=758 | | 42=7t | | 17-x=5+6 | | 5b+4=6b-4 | | 3-6x=4x+0 | | 4(2x)=100 | | 42x-45=-72 | | 5x-1+9x=4x-7 | | (6+3x)=x-18 | | 6n+4=28-11 | | 4w^2+12w+9=1169 | | x^2-6x+9=64 | | y+6x=3 | | 7x+3y-8=4 | | 20w^2-31w+12=0 | | 16a^2-70a+49=0 | | 1x+2=-6 | | -4x^2=9x | | 5a+3(216+a)=888 | | 4y-7-6y-2= | | -2-2(-7x+7)=82 | | -15=-12+3r | | -7(1k-8)+2k= |

Equations solver categories